LANGUAGE TOOLS THAT CREATE MEANING DIVERSITY IN ARTISTIC SPEECH - Mammadova Melek Hidayat gizi (Research Focus International Scientific Journal, 2025)
In the dictionary modern Azerbaijani language words separated on group by their значнию ​To one from such group belong words that have opposite friend friend These are the meanings. group verbs - antonyms, avaes different species значения, бесплатно и по degrees contradictions. Being full and relative, they are occupy important место в lexico-semantic system Azerbaijani language​ Emergence, development and formation Антонимов в языке connected with contradictory character subjects, events and actions material mira, to which they belong to Meat contradictions are expressed opposite in words. Exactly therefore they are performing basic factor education Antonimov. Here also plays role experience social life people. In his life people understand signs and qualities objects and events material world and distinguish their friend fire друга. Concepts, expressed antonyms, connected with work activity человека, образме life, spiritual with the world, his my attitude to my surroundings peace. This group word serves more accurate and emotional expression thoughts. Here why antonyms are playing big role in proverbs and wisdom in expressions. Some antonyms are playing important role in education complex word​. These group word also they contrast. For example, friend-enemy, white-black, cold-hot, summer-winter, etc. d. Stylistic shades and features created​ antonyms in art language, quite numerous. Because antonyms express anger, through them is being created clear representation of positive and negative on the sides sign and quality. One from stylistic features antonyms is that, that they cause у человека enthusiasm, emotional feeling, artistic and aesthetic taste​. Antonyms are playing big role in the description image and theme the most reach effective expressions ideas. Antithesis arises in art language through antonym. phenomenon antithesis plays important role in disclosure character depicted subject. In his center contrast. Thank you to this in art language is attached special stylistic effect​ and antonym and antithesis are being created by means of words with the opposite meaning. This community applicable to them both of them. В presented article thanks short role information​ Antonyms in lexical-semantic system Azerbaijani language, as well as thanks explanations on selected in examples from oral folk literature.